Study on the factors influencing ecological environment and zoning control: a study case of the Dongting Lake area - Yin, Xiangpeng; Lu, Zhaoyan; Zhang, Benqing (Frontiers in Ecology and Evolution, 2024)
Protecting the ecosystem of the Dongting Lake area is of utmost importance for maintaining ecological balance and achieving human well-being. This study identifies the key factors influencing the remote sensing based ecological Index (RESI) in the Dongting Lake area based on the spatial and temporal evolution characteristics of the RESI and environmental changes and anthropogenic disturbance factors. The priority zoning for ecological restoration was delineated in combination with the anthropogenic composite index (ACI). By exploring the influence of anthropogenic disturbances on RESI, the zoning locations were determined using spatial statistics and linear regression methods. The overall RESI of the Dongting Lake area showed a decline from 2001 to 2020, with the mean value decreasing from 0.52 to 0.48. High-quality zones were mainly located in mountainous and forested areas, while low-quality zones were mainly distributed in more developed cities in the east urban area. Anthropogenic factors were the main reasons for the decline in the ecological environment, while natural factors showed a positive correlation with RESI.